Differential Effects of Focused Attention and Open Monitoring Meditation on Autonomic Cardiac Modulation and Cortisol Secretion - Ooishi, Yuuki; Fujino, Masahiro; Inoue, Vimala; Nomura, Michio; Kitagawa, Norimichi (Frontiers in Physiology, 2021)
Mindfulness-based interventions (MBIs) have been used widely as a useful tool for the alleviation of various stress-related symptoms. However, the effects of MBIs on stress-related physiological activity have not yet been ascertained. MBIs primarily consist of focused-attention (FA) and open-monitoring (OM) meditation. Since differing effects of FA and OM meditation on brain activities and cognitive tasks have been mentioned, we hypothesized that FA and OM meditation have also differing effects on stress-related physiological activity. In this study, we examined the effects of FA and OM meditation on autonomic cardiac modulation and cortisol secretion. Forty-one healthy adults (aged 20–46 years) who were meditation novices experienced 30-min FA and OM meditation tasks by listening to instructions. During resting- and meditation-states, electrocardiogram transducers were attached to participants to measure the R-R interval, which were used to evaluate heart rate (HR) and perform heart rate variability analyses. Saliva samples were obtained from participants pre- and post-meditation to measure salivary cortisol levels. Results showed that FA meditation induced a decrease in HR and an increase in the root mean square of successive differences (rMSDD). In contrast, OM meditation induced an increase in the standard deviation of the normal-to-normal interval (SDNN) to rMSSD ratio (SDNN/rMSSD) and a decrease in salivary cortisol levels. These results suggest that FA meditation elevates physiological relaxation, whereas OM meditation elevates physiological arousal and reduces stress.